A 3D microstructure based resistor network model for the electrical resistivity of unidirectional carbon composites. (15th December 2015) - Yu, Hong; Heider, Dirk; Advani, Suresh
Abstract: Continuous carbon fiber reinforced polymers (CFRP) exhibit high anisotropy in electrical resistivity. Fiber conductivity and fiber volume fraction governs the resistivity along the fiber direction while the role of fiber undulation and spacing need to be explored when determining electrical properties perpendicular to the fiber direction. A 3D resistor network model is formulated to predict the electrical conductivity of unidirectional (UD) single layer CFRP as a function of the electrical material properties and microstructural parameters such as fiber spacing and waviness. The sensitivity study reveals that fiber waviness is the key factor determining the electrical resistivity of UD CFRP in the transverse direction. Predictions using the proposed model are in good agreement to reported experimental data.